ANALYSIS OF THE EFFECT OF LIQUID VISCOSITY ON ROLLING CONTACT FATIGUE CRACK PROPAGATION OF RAIL - WANG PengPeng; GUO Jun; LIU QiYue; WANG WenJian (Jixie qiangdu)
Based on Reynolds equation and finite element method,the pressure distribution of fluid penetrating into the rail surface crack was calculated by the two-dimensional wheel/rail rolling contact model. Then the stress intensity factor of the crack tip was analyzed,and the effect of fluid viscosity on the rolling contact fatigue crack growth was studied. The results show that the crack propagation mode transforms from type Ⅱ to typeⅠ in the presence of liquid on the surface of the rail,and the liquid that penetrates into the crack is more likely to cause material peeling. The greater the viscosity,the larger the average crack propagation angle,and the propagation path changes from smooth to tortuousthe. When the viscosity is constant,the larger the initial angle of crack,the lower the crack growth rate. And with the increase of viscosity,the crack growth rate decreases.